THE EFFECT OF INERTER ON TUNED MASS DAMPER INERTER (TMDI) TO RESPONSE STRUCTURE EXCITED BY EARTHQUAKE - Niar Sitanggang, Ansadilla
Tuned Mass Damper (TMD) is damper with simple concept, therefore until now the usage of this kind of damper is still popular. However, in reality, when adding some mass in a structure system will affect the structural strength and space availability for placing the TMD. Therefore, there is some effort to keep using TMD with minimal mass. This is the reason to initiate for including inertia to TMD system because inertia is another form from the mass. Inertia and mass have the same meaning which is the ability of an object to maintain their position. Inertia can be found in a system that made by Smith called inerter. This system can make inertia through mechanical movement that can help object to hold its position. The inerter itself consists of two terminals and receive force in acceleration on its both terminals so as the mechanical movement, instead of influenced by one terminal only, both terminals will affect each other to cause the motion. Because of the benefits that stated before, then will create a system combining TMD and inerter named Tuned Mass Damper Inerter (TMDI). Marian and Giaralis have found this idea and have tried to use it in high rise building excited by the wind. Nevertheless, trying the effectiveness of TMD on wind excitation is not enough, reckon that much of structure failures caused by earthquake. According to that situation, in this research, discuss about inerter’s effect on TMDI disturbed by earthquakes. For demonstrate effect from inerter in TMDI, that damper system will assemble in 12th building formed from concrete. With optimized the response structure function specifically displacement, solution of TMDI design will face some numerical calculation with estimated design parameters that are frequency ratio (f) and damping ratio (?). That optimization will be done in every variation mass of TMDI. Moreover, it is because inerter can accept acceleration on both of its terminals, then inerter will attached to lower floors where TMDI is placed. That is the difference between TMD and TMDI because with the inerter can receive acceleration either from TMDI itself or with the attachment floor. The optimization brings in a principal that f is getting closer natural frequency with the value of ???? is increasing. Meanwhile, when the value of f is rising, then ? will drop. Besides parametric design, the location of TMDI attached to others floor is a matter that must be considered. In this case study, if TMDI attached to 12th floor down to 7th then the response structure will climb or equal to response structure without inerter on TMD. With TMDI attached with minimal on 6th floor, response structure consisting of displacement, acceleration, and velocity, which each of its downturn by 50%, 41%, and 36%. The reduction of response structure that have stated happen if the earthquake excitation would come in accordance with the earthquake plan which is Hokkaido earthquake. Structure response that using TMDI show that the bigger acceleration deviation between both terminal inerter, the better performance of TMDI for suppressing response. That differentiates of acceleration indicates TMDI and the attachment floor is getting further. In addition to better structure response, TMDI itself don’t need to add big mass. In the example for decreasing 20% of response structure, TMDI will need mass 4 times lighter from TMD mass.